104 Reducing unwarranted variations in frequency of coronary angiographies in germany by describing, understanding and modifying local practice. (20th August 2018) - Gerlach, Navina; Schlößler, Kathrin; Steinbuck, Joana; Bleek, Julian; Günster, Christian; Marschall, Ursula; Schneider, Udo; Horenkamp-Sonntag, Dirk; Sundmacher, Leonie; König, Hans-Helmut; Zeymer, Uwe; Schneider, Steffen; et al.
Abstract : Objectives: Germany has one of the highest numbers of coronary angiography worldwide. Nevertheless, we find a great variation between German regions for both, diagnostic coronary angiographies and percutaneous coronary interventions (PCI). We assume that this variation is not only due to variation in morbidity but also reflects factors such as guideline adherence, physician-patient communication and access to care. In this mixed method project, we aim to first describe the variation of coronary angiographies and PCIs in different German regions. Secondly, we explore current practices and motives for (non-)adherences to guidelines in the diagnostic process of patients with suspected CHD. Based on these results, we consequently plan to develop a complex intervention (treatment pathway) to improve guideline adherence and thus appropriateness of coronary angiography. Method: The projects will be organized according to the recommendation of the Medical Research Council for the development and evaluation of complex interventions. The first study will use descriptive methods based on routine data of three German Health Care Insurances and registry data to describe status quo and associated factors of coronary angiography. The second study will use qualitative methods to understand barriers and facilitators of guideline adherence and medical decision making. Furthermore, we will discuss variations in care and thereby identify implementation targets for the planned treatment pathway. Based on this information, we will develop local treatment pathways in four selected regions. Relevant peers will develop the local pathway in group discussions. Using this bottom-up approach, we directly address implementation challenges.